AUDIO – VIDEO LINK KAO SREDSTVO ZAŠTITE POSEBNO OSETLJIVOG SVEDOKA I FAKTOR URAVNOTEŽENJA POLOŽAJA OKRIVLJENOG - Ivana Miljuš (Revija za kriminologiju i krivično pravo)
The subject of this paper is the dual function of audio - video link in criminal proceedings in which vulnerable witnesses are examined - protection of witnesses and victims and ensuring the exercise of the defendant ‘s right to examine witnesses. In the first part of the paper, the author analyzes the concept of “audio - video link”, its legal nature, characteristics, roles and basic risks. The second part of the paper explores the normative and practical foundations of the protection of minors in criminal proceedings. The third part of the paper deals with the requirement to establish and maintain a balance of legitimate interests of enabling testimony and effective punishment, protection of the physical and mental integrity of witnesses and the right to defense. “In the balance test” of the European Court of Human Rights, the audio-video link is a “positive measure” of the state and a “counterbalancing factor”. The subject of the paper is also the normative regulation of an especially vulnerable witness. The aim of this paper is to point out the importance of proper use of technical devices for transmitting images and sound during the examination of especially vulnerable witness, but also its potential risks, possible proposals to improve the normative basis for their application and basic principles of audio - video link in criminal procedure.